The Effect of Ethnicity on 2D and 3D Frontomaxillary Facial Angle Measurement in the First Trimester - Jennifer Alphonse; Jennifer Cox; Jill Clarke; Philip Schluter; Andrew McLennan (Hindawi Limited, 2013)
Objectives. To determine the existence and extent of ethnic differences in 2D or 3D fetal frontomaxillary facial angle (FMFA) measurements. Methods. During routine 11-14 weeks nuchal translucency screening undertaken in a private ultrasound practice in Sydney, Australia, 2D images and 3D volumes of the fetal profile were collected from consenting patients. FMFA was measured on a frozen 2D ultrasound image in the appropriate plane and, after a delay of at least 48 hours, was also measured on the reconstructed 3D ultrasound volume offline. Results. Overall 416 patients were included in the study; 220 Caucasian, 108 north Asian, 36 east Asian and 52 south Asian patients. Caucasians had significantly lower median FMFA measurements than Asians in both 2D (2.2°; ) and 3D (3.4°; ) images. Median 2D measurements were significantly higher than 3D measurements in the Caucasian and south Asian groups ( and ), but not in north and east Asian groups ( and ). Conclusions. Significant ethnic variations in both 2D and 3D FMFA measurements exist. These differences may indicate the need to establish ethnic-specific reference ranges for both 2D and 3D imaging.